Success Factors in Construction Management of Local Administrative Organizations in Mueang District, Phetchabun Province: an Exploratory Factor Analysis - Suwansumrit, Pattana; Pongpeng, Jakrapong (Srinakharinwirot University Engineering Journal, 2025)
This study aims to examine the success factors in construction project management of local administrative organizations in Mueang District, Phetchabun Province, using Exploratory Factor Analysis (EFA). The sample consisted of 240 respondents from both public and private sectors. A questionnaire was employed as the research instrument, and data were analyzed using descriptive statistics, EFA, and the Mann-Whitney U test for comparing group perceptions. The findings revealed four major groups of success factors: (1) overall project management, (2) scope and risk management, (3) core objective management, and (4) supportive management functions, comprising a total of 12 sub-factors. Additionally, significant differences in perspectives between the public and private sectors were identified in several aspects. These findings highlight the importance of designing construction management systems that account for sector-specific characteristics to enhance the efficiency and sustainability of local projects